Catholic institutions in Argentina from the twentieth century to the present: consolidation, evidences of decline, and crisis—a statistical analysis - Suárez, Ana Lourdes (2023)
Fil: Suárez, Ana Lourdes. Pontificia Universidad Católica Argentina; Argentina